Making sense of AIDS : culture, sexuality, and power in Melanesia - Butt, Leslie, 1960-; Eves, Richard (University of Hawaiʻi Press, 2008)
In Melanesia, rates of HIV infection are among the highest in the Pacific and increasing rapidly, with grave humanitarian, development, and political implications. There is a great need for social research on HIV/AIDS in the region to provide better insights into the sensitive issues surrounding HIV transmission. This collection, the first book on HIV and AIDS in the Pacific region, gathers together stunning and original accounts of the often surprising ways that people make sense of the AIDS epidemic in various parts of Melanesia. The volume addresses substantive issues concerning AIDS and contemporary sexualities, relations of power, and moralities--themes that provide a powerful backdrop for twenty-first century understandings of the tensions between sexuality, religion, and politics in many parts of the world.